Evaluation of the efficacy of potassium nitrate and sodium fluoride as desensitizing agents during tooth bleaching treatment—A systematic review and meta-analysis - Wang, Yining; Gao, Jinxia; Jiang, Tao; Liang, Shanshan; Zhou, Yi; Matis, Bruce A. (Journal of dentistry, 2015)
This meta-analysis was performed to evaluate the efficacy of potassium nitrate and sodium fluoride as desensitizing agents during tooth bleaching treatment. An electronic systematic literature search was conducted in Cochrane Center Register of Controlled Trials, MEDLINE (PubMed) and EmBase in April, 2014 in English and without time restrictions. Study information extraction and methodological quality assessments were accomplished by two reviewers independently. Methodological quality was assessed by using the “Criteria for judging risk of bias in the ‘Risk of bias’ assessment tool”. Dichotomous data was summarized by odds ratio (OR) with 95% confidence interval (CI) and continuous data was summarized by mean difference (MD) or standardised mean difference (SMD) with 95% confidence interval (CI). Statistical analyses were carried out by using Review Manager 5.2. For evaluation of percent of patients experiencing tooth sensitivity (POTS), the pooled OR of desensitizers vs. placebo was 0.45 (95% CI: 0.28–0.73, P=0.29). The pooled SMD of desensitizers vs. placebo was −0.47 (95% CI: −0.77 to −0.18, P=0.13) in evaluation of level of tooth sensitivity (LOTS). The results of shade evaluation remained inconsistent by evaluating subjective shade guide unit difference (ΔSGU or SGU) and objective colour difference (ΔE). This meta-analysis was performed to evaluate the efficacy of desensitizing agents, potassium nitrate and sodium fluoride, for tooth bleaching treatments. Potassium nitrate and sodium fluoride reduce tooth sensitivity while no consistent conclusion of tooth colour change was found. Tooth sensitivity is a typical side effect associated with tooth bleaching procedures. Potassium nitrate and sodium fluoride are used widely to treat tooth sensitivity. This meta-analysis was performed to evaluate the efficacy of potassium nitrate and sodium fluoride as desensitizing agents during tooth bleaching treatment.